RIVERBANK EROSION IN PART OF TIBO VILLAGE, DONGGALA REGENCY - Rendra Zainal Maliki (GeoEco, 2022)
This study aims to identify riverbank erosion in some Tibo villages, Sindue Tambusabora District, Donggala Regency. This type of research is descriptive qualitative with a spatial approach. The data analysis technique used in this study includes a qualitative descriptive analysis in the form of a unit analysis of the area of landform from the fluvial process in Tibo Village, Sindue Tambusabora District, Donggala Regency. The data used in this study include primary data and secondary data. Primary data are the results of field ground checks and direct measurements, while secondary data are Landsat 8 OLI images and RBI maps of 1:50,000 scale 2015-65. This type of research is descriptive qualitative with a spatial approach. The data analysis technique used in this study includes a qualitative descriptive analysis in the form of a unit analysis of the landform area from which the fluvial process originated in the village of Tibo. Mild to moderate erosion and sedimentation rates. Erosion of cliffs is very high, especially at the bend of the river where erosion occurs due to high river discharge so that many charred rivers are found in Tibo village due to high erosion and sedimentation.